Assessing targeted longer-term refinancing operations: Identification through search intensity - Olli-Matti Laine; Jaakko Nelimarkka (Bank of Finland, 2023)
We evaluate the effects of targeted credit injections of the central bank in the euro area. The aggregate policy impacts of credit easing on financial markets, bank lending and key macroeconomic variables are measured with a novel identification approach based on high-frequency web search data. Our results suggest that the targeted longer-term refinancing operations of the European Central Bank between 2014 and 2021 eased credit conditions in financial markets and had economically and statistically significant positive effects on GDP growth, bank lending and firm investment.
Keywords: C36; E42; E51; E52; E58; G31; 330; Monetary policy; High-frequency identification; TLTRO; Bank lending